1994
DOI: 10.1007/bf01175749
|View full text |Cite
|
Sign up to set email alerts
|

Debris flow modeling: A review

Abstract: A debris flow represents a mixture of sediment particles of various sizes and water flowing down a confined, channel-shaped region (e.g., gully, ravine or valley) down to its end, at which point it becomes unconfined and spreads out into a fan-shaped mass. This review begins with a survey of the literature on the physical-mathematical modeling of debris flows. Next, we discuss the basic aspects of their phenomenology, such as dilatancy, internal friction, fluidization, and particle segregation. The basic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(77 citation statements)
references
References 48 publications
0
76
0
1
Order By: Relevance
“…Generally speaking, the friction term can be computed according to three different schemes: (a) one-phase model, accounting for the overall resistance behaviour of the solid-fl uid mixture; (b) two-phase model, considering separately the contribution to the resistance force associated with liquid and solid phases; (c) multi-layer model, assuming a number of superimposed fl owing layers, each one with a specifi c fl ow resistance behaviour. An appreciable review of these models can be found, as an example, in [13], whereas signifi cant information about two-phase models can be found in [15].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the friction term can be computed according to three different schemes: (a) one-phase model, accounting for the overall resistance behaviour of the solid-fl uid mixture; (b) two-phase model, considering separately the contribution to the resistance force associated with liquid and solid phases; (c) multi-layer model, assuming a number of superimposed fl owing layers, each one with a specifi c fl ow resistance behaviour. An appreciable review of these models can be found, as an example, in [13], whereas signifi cant information about two-phase models can be found in [15].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This formulation is kept in the present work, while the innovation stands in the numerical implementation, since a fi nite volume method based on Roe's scheme is used instead of the MacCormack fi nite difference method [9,10]. The main reason is the necessity of correctly capturing front wave propagation speed in case of initially dry bed, for which Riemann solvers-based techniques are recommended [11][12][13][14]. The second reason is the intention to verify if the model stability features are kept even if the numerical implementation radically changes.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the video recorded images of some events (Deganutti et al, 1998) we have assumed that the coarse fraction gives to the overall mixture a rather high drainage capability, although no experimental measurements are available on this aspect. We thus deem that the effect due to the excess-pore fluid pressure (Hungr, 1995;Hutter et al, 1996;Iverson, 1997) can be neglected. This hypothesis is equivalent to state that the excess pore pressure, if present, dissipates in time-scales much smaller than the time scale of the water-sediment propagation.…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…Two-phase models are similar except that they separate the flow material into solid and fluid components, positing separate mass and momentum balances and therefore applying different rheological laws for each phase. The components are coupled via momentum exchanges [Hutter et al, 1996].…”
Section: Introductionmentioning
confidence: 99%